2002
DOI: 10.1034/j.1399-0039.2002.590603.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1 and DQB1 allele distribution in the Muong population exposed to malaria in Vietnam

Abstract: The distribution of 30 HLA-DRB1 alleles in 85 individuals and of 10 HLA-DQB1 alleles in 91 individuals of the Viet Muong population was studied and compared with those of nine other Asian populations, including 103 Viet Kinh belonging to the major ethnic group in Vietnam. In terms of genetic distance, our data are consistent with a close ethnogeographic relationship between Viet Muong, Buyi and Dai Lue, two Southern Chinese ethnic groups. Conversely, these three populations are distant from the Northern Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…At the HLA-B locus, B*1301 showed high frequencies in Jinuo and Wa as well as in Singapore Chinese, Maonan, and South Han; however it is rare in Japanese and Korean [27,36]. At the HLA-DRB1 locus the dominant allele DRB1*1502 in Jinuo and Wa showed high frequencies in Thai, Thai Black, Thai Dai Lue, Thai Northeast, and Munong Vietnamese [37]. These allele distributions showed that Jinuo and Wa populations possessed the southern Asian characters, which is further supported by the distribution of the haplotyes.…”
Section: Discussionmentioning
confidence: 93%
“…At the HLA-B locus, B*1301 showed high frequencies in Jinuo and Wa as well as in Singapore Chinese, Maonan, and South Han; however it is rare in Japanese and Korean [27,36]. At the HLA-DRB1 locus the dominant allele DRB1*1502 in Jinuo and Wa showed high frequencies in Thai, Thai Black, Thai Dai Lue, Thai Northeast, and Munong Vietnamese [37]. These allele distributions showed that Jinuo and Wa populations possessed the southern Asian characters, which is further supported by the distribution of the haplotyes.…”
Section: Discussionmentioning
confidence: 93%
“…The predominance of HLA-DQB1*0301 and HLA-DQB1*0501 has been previously observed among the Viet Kinh population which represents the majority of individuals living in Vietnam (85%) (55) and the Viet Muong population (56) , being among the 54 minor ethnic groups representing the rest of the Vietnamese population. The quite homogeneous HLA-DQB1 background observed in Vietnamese women, which means a limited repertoire of HLA-DQB1 molecules for antigenic presentation, may constitute a risk factor not only for HPV but also for other infectious agents in this population.…”
Section: Discussionmentioning
confidence: 87%
“…The distribution of the B*5301 allele is restricted to African populations but B*1513 is present in Southeast Asian populations including all four indigenous Malaysian groups in this study. Busson et al (29) also suggested that HLA‐DQB1*0502 may infer protective effects against Plasmodium falciparum infections in the Muong of Vietnam. DQB1*0502 also happens to be frequent not just in the four indigenous Malaysian groups but also other Southeast Asians.…”
Section: Discussionmentioning
confidence: 99%